Development of Digital-Based Service Marketing Management: A Conceptual Framework - Henry Sumurung Octavian; Febry Lodwyk Rihe Riwoe; Hageem Che-Ni (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid advancement of digital technologies has transformed service marketing, requiring businesses to adopt innovative, data-driven strategies to enhance customer engagement and competitive advantage. This study proposes a conceptual framework for digital-based service marketing management, integrating insights from existing literature on customer-centric digital strategies, AI-driven marketing approaches, multi-channel integration, and data-driven decision-making. The research explores key success factors, including digital infrastructure, evolving consumer expectations, and ethical considerations in the implementation of digital marketing strategies. Using a conceptual research design, this study conducts a systematic literature review of scholarly articles, books, and industry reports to synthesize key theories and models, such as SERVQUAL and the Technology Acceptance Model (TAM). A proposed framework is introduced to illustrate the relationships between digital marketing strategies, customer engagement, and business performance. The findings contribute to academic research by expanding service marketing literature and offer practical implications for businesses navigating digital transformation.While this study provides theoretical insights, it is limited by the lack of empirical validation. Future research should focus on testing the proposed framework across different service industries and examining emerging digital trends, such as metaverse marketing, blockchain, and AI-driven hyper-personalization. By addressing these areas, researchers and practitioners can develop more effective, ethical, and customer-centric digital service marketing strategies in an increasingly dynamic business environment. Keywords: Digital Service Marketing, AI, Big Data, Customer Engagement, Digital Transformation, Conceptual Framework